Tissue Engineering and Regeneration Therapy: A Boon for Periodontal Research - Gatha Mohanty1, Rinkee Mohanty2, Manoj Kumar3, Saurav Panda3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Complete regeneration of the periodontium is the aim of any successful periodontal treatment. RecentTechnologies have come up with many advances like cell-based therapy, peptides, genetic transfer,scaffolds, bone anabolics, and above all lasers. Four basic elements are required for periodontal repair andregeneration that includes adequate blood supply and wound stability, a source of bone and ligament formingcells, a supporting scaffold, and growth factors to regulate cell migration, synthesis and angiogenesis forrevascularization of the site. The newer technologies not only offer unique opportunities but also enhancethe predictability of regenerative procedures.